Nitrogen-doped hollow carbon spheres with large mesoporous shells engineered from diblock copolymer micelles - Tang, J.; Liu, Jian; Salunkhe, R.; Wang, T.; Yamauchi, Y. (ROYAL SOC CHEMISTRY, 2016)
Nitrogen-doped hollow carbon spheres with engineered large tunable mesoporous (~20 nm) shells were successfully synthesized for the first time by using the colloidal silica and the diblock copolymer PS-b-PEO as the dual-template and dopamine as the precursor. The unique structural properties enable them to be promising materials as adsorbents, catalyst supports, electrode materials, drug delivery carriers and hosts for active substances.